Determining kinetic constants for the biological treatment of sucrose-based wastewater using mixed-culture seeding microorganisms - Bancud, Amy Ambrocia G. (College of Engineering, University of the Philippines Diliman, 2015)
In this study, aerobic treatment of sucrose-based wastewater was carried out using mixed-culture seeding microorganisms. Experimentations were performed using batch reactors. Two experimental set-ups were done to simulate: (1) Attached Growth Process and (2) Suspended Growth Process. The effect of inoculum concentration, acclimation time for the microorganism and initial substrate concentration on reduction of organic matter were determined by measuring the COD of the substrate. Kinetic study was performed using the Michaelis-Menten model for enzyme kinetics since almost all biological processes can be explained by this model. Initial rate of reaction, in terms of COD reduction, was computed for the different initial substrate concentrations. The reaction constants for the Michaelis-Menten equation, Km and Vmax, were determined using the three known methods of linearizing the data: (a) Lineweaver-Burk plot, (b) Eadie-Hofstee plot, and (c) Hanes-Woolf plot. The resulting Km and Vmax values for Attached Growth Process were: Km 350 mg/L, Vmax = 11.325 mg/L-hr., while for Suspended Growth Process the values were: Km 1346 mg/L, Vmax- 22.321 mg/L- hr. The aerobic treatment of the sucrose-based wastewater by the mixed-culture seeding microorganisms follows the Michaelis-Menten model.